2016
DOI: 10.5935/0103-5053.20160155
|View full text |Cite
|
Sign up to set email alerts
|

Use of Lignins from Sugarcane Bagasse for Assembling Microparticles Loaded withAzadirachta indicaExtracts for Use as Neem-Based Organic Insecticides

Abstract: Microcapsules of sugarcane bagasse lignin loaded with organic extracts of neem (Azadirachta indica) were prepared and evaluated as potential bioinsecticides. Lignins were extracted and modified by oxidation and acetylation reactions providing different biopolymers. Afterwards, they were characterized through several analytical techniques. The formulations were initially prepared as colloidal suspension of lignin nanoparticles, which were then spraydried. The products were submitted to quality control protocols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
1
13
0
4
Order By: Relevance
“…The current research has shown the efficiency of different formulations of neem-based bioinsecticides in the laboratory, and the most efficient doses are promising to be further assessed under greenhouse and field conditions. It is noteworthy that lignin-microencapsulated neem extract formulation is protected by a lignin layer, which prevents the rapid photo and thermal degradation of the active compound azadirachtin (Costa et al 2017); this is considered to be a limitation for the use of botanical insecticides in crop protection. Therefore, the lignin-microencapsulated Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current research has shown the efficiency of different formulations of neem-based bioinsecticides in the laboratory, and the most efficient doses are promising to be further assessed under greenhouse and field conditions. It is noteworthy that lignin-microencapsulated neem extract formulation is protected by a lignin layer, which prevents the rapid photo and thermal degradation of the active compound azadirachtin (Costa et al 2017); this is considered to be a limitation for the use of botanical insecticides in crop protection. Therefore, the lignin-microencapsulated Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Lignin-microencapsulated neem extract. Lignin used in this assay was obtained from sugarcane bagasse by sodapulping process as previously described by Costa et al (2017). To prepare the formulation lignin-microencapsulated neem extract the following components first were added in separate beakers: 0.6 g fractions of ethyl acetate from neem crude ethanolic extract, 0.67 g Tween ® 80, 3.5 g commercial neem oil (Baraúna, Catanduva, SP, Brazil), and 50 mL distilled water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained data reflect the growing interest and potential of green and sustainable methods to separate natural products from waste. One tendency observed in particular was the innovative ways to remove (integrating extraction, purification and/or modification in the same integrated system) and use such compounds in more contemporary sectors, promoting human and environmental health instead of general and old-fashioned remediation [ 19 , 38 ]. As a result, new applications for food, nutraceutical, and agricultural sectors have been further explored, based on their advantageous properties as natural colorants, flavors, aromas, antioxidants, antifungals, bioformulations (bio-pesticides) or simply their use as precursors to generate other compounds for similar uses.…”
Section: High Value-added Approaches For Green and Sustainable Separamentioning
confidence: 99%
“…9 O objetivo principal da hidrólise alcalina à alta temperatura e pressão é solubilizar a hemicelulose, permitindo o acesso à lignina nos demais procedimentos do tratamento. 15 Além disso, após a extração, a lignina pode ser aplicada em diversas áreas, gerando produtos de valor agregado. Um exemplo disto é o conceito de biorrefinaria que visa a transformação de biomassa em compostos úteis, através da combinação de diferentes processos e tecnologias, como combustíveis, pesticidas, polímeros e outros produtos químicos.…”
Section: Introductionunclassified